Prayer, Dreams, and Sex: A Showcase of an AI‐Augmented Distant Reading of 20 Thousand E‐Fatwas - Svensson, Jonas (CyberOrient, 2024)
This article provides a methodologically oriented case study of the application of Large Language Models (LLMs) in Islamic studies. Its empirical focus is on 20 thousand e‐fatwas from the website askimam.org. The study demonstrates how LLMs, here represented by the open‐source tool BERTopic, can significantly augment a process of distant reading. The research focuses on a topic modelling revealing insights into recurring concerns evident from the questions posed by believers in fatwas. It also provides an example of further, post‐topic modelling and analysis focusing on thematic variations across questions from different geographical regions. The article argues for the potential of LLMs to reshape research methodologies, offering faster, more comprehensive, and nuanced analyses of large datasets.